THE RELATIONSHIP BETWEEN TOURIST ARRIVALS AND ACCOMODATION IN ROMANIAN REGIONS. A PANEL DATA APPROACH - Simionescu, Mihaela (Revista de turism - studii și cercetări în turism, 2017)
This research is a novelty for the literature regarding tourism demand modeling in Romania. Panel data approach has been applied to analyze the relationship between tourist arrivals and the establishments of tourists’ reception with functions of tourists' accommodation in the eight Romanian regions (Nord-West region, Central region, Nord-East region, South-East region, South-Muntenia region, Bucharest-Ilfov region, South-West Oltenia and West regions). According to panel VAR Granger causality test, the establishments of tourists’ reception with functions of tourists' accommodation are a cause for tourist arrivals, but the relationship is not reciprocal. A valid fixed effects model was built and an increase in the number of establishments of tourists’ reception with functions of tourists' accommodation with one establishment increased in average the number of tourist arrivals with around 293 people in Romanian regions over the period 1990-2015. According to panel vector-autoregressive model, the tourist arrivals in the current period were positively influenced by the establishments of tourists’ reception with functions of tourists' accommodation and tourist arrivals in the previous period.